Glomerular diseases in a Hispanic population: review of a regional renal biopsy database - Arias,Luis Fernando (2009)
CONTEXT AND OBJECTIVE: Epidemiological data provide useful information for clinical practice and investigations. This study aimed to determine glomerular disease frequencies in a region of Colombia and it represents the basis for future studies. DESIGN AND SETTING: Single-center retrospective analysis at the University of Antioquia, Colombia. METHODS: All native renal biopsies (July 1998 to December 2007) were reviewed, but only glomerular diseases were analyzed. The diagnosis of each case was based on histological, immunopathological and clinical features. RESULTS: A total of 1,040 biopsies were included. In 302 cases (29.0%), the patient's age was < 15 years. Primary glomerular diseases were diagnosed in 828 biopsies (79.6%) and secondary in 212 (20.4%). The most common primary diseases were focal and segmental glomerulosclerosis (FSGS) (34.8%), immunoglobulin A (IgA) nephropathy (IgAN) (11.8%), membranous glomerulonephritis (MGN) (10.6%), minimal change disease (MCD) (10.6%), crescentic glomerulonephritis (GN) (5.6%), and non-IgA mesangial proliferative GN (5.6%). Postinfectious GN represented 10.7% of the diagnoses if included as primary GN. Lupus nephritis corresponded to 17.8% of the entire series. In adults, the order of the most frequent primary diseases was: FSGS, IgAN, MGN, crescentic GN and MCD. In children (< 15 years), the most frequent were: FSGS, postinfectious GN, MCD, non-IgA mesangial proliferative GN, endocapillary diffuse GN and IgAN. CONCLUSIONS: As among Afro-Americans, FSGS is the most frequent type of glomerulopathy in our population, but in our group, there are more cases of IgAN. The reasons for these findings are unclear. This information is an important contribution towards understanding the prevalence of renal diseases in Latin America.